THE IMPLEMENTATION OF LEARNING CELL TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION - KARTINI KARTINI (LP3M Universitas Muhammadiyah Muara Bungo, 2018)
The objectives of the research were to know the implementation of learning cell technique to improve students’ reading comprehension and to find out the students’ perception of using learning cell technique. This research design was classroom action research at the seventh grade students of SMPN 2 Tangerang. The participants of this research were 34 students. They were consisting of 17 male students and 17 female students of seventh grade students at SMPN 2 Tangerang. The data collection techniques in this research were written tests, observation, questionnaire and interview. The interview was done for 20 students of thirty four students at the seventh grade students of SMPN 2 Tangerang. The data collective and analysis used qualitative data which was supported by quantitative data. This research was done from October to November 2017. The finding of the research showed that implementation of learning cell technique could be effective and can improved students’ reading comprehension. It can be seen from the finding of students score from cycle 1 to cycle three. The data showed the students’ tests score improved. The students who passed the standard score (KKM) in cycle one was 56.7%, cycle 2 was 67.7% and cycle 3 was 96.8%.